1969
DOI: 10.1111/j.1365-2141.1969.tb01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Phospholipid and Fatty Acid Composition of Human Erythrocytes and Platelets

Abstract: Summary. The phospholipid and fatty acid composition of the diacyl and plasma‐logen derivatives of the choline and ethanolamine phosphoglycerides of human erythrocytes and platelets have been compared. No distinctly new information on the phospholipid composition of either cell was uncovered. However, the fatty acid composition studies showed rather distinct patterns among the four fractions, and between the cell types. The possible biosynthetic mechanisms responsible for and physiological meaning of these di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(45 citation statements)
references
References 30 publications
7
38
0
Order By: Relevance
“…It was suggested that the diglyceride produced may participate in platelet secretion (19 Tables I and II) and, to a lesser extent, of LPC, combined with an apparent decrease in PE and PC, indicate the presence of phospholipase A2 activities distinct from those of the aforementioned PI-specific enzymes. We noted that LPE contained a smaller percentage of aldehydes (Table I) than was reported previously on the 1-position of platelet PE (10,11,25). This may suggest that the LPE was generated by a phospholipase A2 acting more readily upon the diacyl form than upon the plasmalogen form of PE, a phenomenon also reported by Jesse and Cohen (30) in previous studies with platelet membrane preparations.…”
Section: Resultssupporting
confidence: 40%
See 3 more Smart Citations
“…It was suggested that the diglyceride produced may participate in platelet secretion (19 Tables I and II) and, to a lesser extent, of LPC, combined with an apparent decrease in PE and PC, indicate the presence of phospholipase A2 activities distinct from those of the aforementioned PI-specific enzymes. We noted that LPE contained a smaller percentage of aldehydes (Table I) than was reported previously on the 1-position of platelet PE (10,11,25). This may suggest that the LPE was generated by a phospholipase A2 acting more readily upon the diacyl form than upon the plasmalogen form of PE, a phenomenon also reported by Jesse and Cohen (30) in previous studies with platelet membrane preparations.…”
Section: Resultssupporting
confidence: 40%
“…In addition, gas chromatographic analysis of methylated samples indicated the presence of a large proportion of dimethylacetal derivatives (Table I). In human platelets measurable amounts of plasmalogens (as dimethylacetals) are found only in the ethanolamine phosphoglyceride class (10)(11)(12) (Table I) suggested that the LPE was formed by a phospholipase A2-like activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatty acid content was quantitated using gas chromatography as described previously. 35 Individual phospholipids were separated on a silica gel H plate using the solvent system chloroform/methanol/acetic acid/water (60:36:9.6:4.8, v/v) and quantitated by phosphate estimation after acid hydrolysis. 36 Statistical Analysis.…”
Section: Methodsmentioning
confidence: 99%